Habit, experience and environment: A pragmatist perspective. (April 2020) - Bridge, Gary
Contemporary discussions of human–environment relations see habits as enabling forces of change (becoming) in contrast to traditional views of habit as routine and restrictive elements of identity (being). Vital life (becoming) is realised in habit through body repetition (Ravaisson) or through material force (Deleuze). This paper argues for the significance of the pragmatist work of John Dewey that shares this dispositional, enabling view of habit, but denies any dualism between life and mechanism. The paper explores Dewey's idea of habits as mechanisms of natural forms of organisation that have different life force, depending on the situational qualities of environment–human transactions. This approach also implicates habit in problematisation. The paper goes on to discuss the implications of pragmatist thinking for understanding human–environment relations and the place that habits have in intervening in and reforming those relations through social activism and public policy.